The Use Of Reciprocal Strategy In Teaching Reading Comprehension - Herlina, Nirma (2014)
This study reports on the use of reciprocal strategy in teaching students' reading comprehension. It aims at elaborating the implementation of reciprocal teaching strategy in the classroom, investigating the effects of the use of reciprocal teaching strategy on the students' reading comprehension, and exploring the students' attitudes toward its implementation. The study employed a quasi-experimental design and involved second graders of senior high school in one public school in Riau, Indonesia. 30 students in one class acted as the experimental group, while 30 students in another class acted as the control group. In the study, the researcher acted as the teacher. The study used three types of data collection techniques including reading comprehension tests; a five-week of classroom observation and a questionnaire. The data was analyzed based on the theories of reciprocal teaching strategy (Palinscar & Brown, 1984; Hartman, 1997; Meyer, 2010, P.41; and Klingner, Vaughn, & Boardman, 2007, p.133-134).The findings showed that the implementation of reciprocal teaching strategy including; (1) teacher demonstration; (2) direct instruction and guided practice; (3) teacher-student group; and (4) students-lead group was effective to enhance the students' reading comprehensions. The data from the reading comprehension test showed that there was a significant difference between the experimental and the control groups in terms of the scores. It can be seen from the result of independent t-test of post-test scores, t-value (t= -3.267, df= 59) was higher than critical value (2.00). Moreover, the data from the classroom observation and the questionnaire demonstrated that the reciprocal strategy used in the experimental group provided three effects to the students' reading comprehension encompassing (1) obtaining clear idea of the concept and of the use of four reading strategies; (2) developing their self-confidence in sharing their ideas; and (3) enjoying learning atmosphere. Apart from that, the results of questionnaire revealed the students' positive and negative attitudes toward the implementation of reciprocal teaching strategy in the classroom. Based on the findings, it is recommended that English teachers apply this strategy to develop better students' reading comprehension.